Enhanced Electrochemical Cu Release from Commercial Cu-Sn Alloys: Fate of the Alloying Elements in Artificial Perspiration. (1st July 2017) - Hutchison, M.J.; Zhou, P.; Ogle, K.; Scully, J.R.
Abstract: Commercially pure Cu (Cu), Cu-4.5Sn-0.1Zn, and Cu-9.7Sn-0.1Zn (wt%) were evaluated for corrosion and cation release in modified artificial human perspiration solution. Open circuit corrosion exposures were conducted for up to 130 hours to determine corrosion rate and the fate of Cu and Sn. Released aqueous ion concentrations were monitored via inductively-coupled plasma − optical emission spectroscopy (ICP-OES). Operando atomic emission spectroelectrochemistry (AESEC) analysis was utilized to elucidate the fate of Cu, whether in oxides or solution and deduce the dominant valence states, Cu(I)/Cu(II), of soluble Cu in artificial perspiration. Sn was not observed as a soluble ionic species within ICP-OES or AESEC limits of detection (LOD). Corrosion products were characterized using grazing incidence X-ray diffraction (GIXRD), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS), and quantified with coulometric reduction (CR). Cu-4.5Sn-0.1Zn displayed the highest corrosion rates in artificial perspiration, followed by Cu-9.7Sn-0.1Zn, and then Cu. Primary corrosion products were Cu2 O, with CuCl as an outer solid product, and an inner layer of SnO2 for Sn-containing alloys. Cu was dissolved as cuprous (Cu + ) ions. Minor Sn alloying in solid solution catalyzed Cu dissolution which is counteracted at higher Sn contents by a passivating layer of SnO2, achieving complete passivity at 10.3 wt% Sn according to graph theory. Cu-9.7Sn-0.1Zn indicated semi-passive behavior, speculated to be due a SnO2 layer and close proximity (9.7 wt%) to this critical value for passivation (10.3 wt%). The effect of alloyed Sn as a dissolution promoter for electrochemical Cu ion release, critical Sn contents for passivity, and subsequent implications of antimicrobial function are discussed. Oxidized Zn was not detected above LOD nor demonstrated any measurable effect on corrosion in artificial perspiration.